Gas chromatography for analysis and estimation of 13C at natural abundance level in fatty acids produced from Aurantiochytrium limacinum, a sustainable source of polyunsaturated fatty acid - Dirir, Amina M.; Chokshi, Kaumeel; Ali, Abdelmoneim H.; Alhanawi, Media; Rommala, Mohan; Hachem, Mayssa (Frontiers in Bioengineering and Biotechnology, 2025)
Aurantiochytrium limacinum (A. limacinum) is a promising microbial source of polyunsaturated fatty acids (PUFAs), particularly Docosahexaenoic Acid (DHA, C22:6n-3). In this study, we first optimized the culture conditions of A. limacinum ATCC MYA-1381 (strain SR21). Cell growth was monitored via optical density, cell counts, and glucose concentration. Cells were harvested at exponential and stationary phases, and lipids were extracted using a green method. Fatty Acid Methyl Esters (FAMEs) were prepared and analyzed using Gas Chromatography-Flame Ionisation Detection (GC-FID). At the exponential phase, DHA was the most abundant (65.6% of total fatty acids) followed by palmitic acid (C16:0) at 34.4%. At the stationary phase, Docosapentaenoic acid (DPA, C22:5n-3) and DHA were the most abundant at 45.4% and 33.9%, before respectively. Myristic acid (C14:0), myristoleic acid (C14:1n-9), palmitic acid (C16:0) were present at 4.6%, 6.2% and 9.9%, respectively. Compound-specific isotope analysis (CSIA) using Gas Chromatography-Combustion-Isotope Ratio Mass Spectrometry (GC-C-IRMS) revealed that all FAMEs had negative δ13C values, indicating depletion in 13C. At the exponential phase, δ13C (‰) of C16:0 and DHA were −16.8 ± 0.2 and −18.5‰ ± 0.1‰, respectively. At the stationary phase, δ13C (‰) of C14:0, C14:1n-9, C16:0, C22:5n-3 and DHA were −10.6 ± 1.1, −11.3 ± 0.1, −11.1 ± 0.2, −8.3 ± 0.2 and −10.6‰ ± 0.1‰, respectively. Overall, our findings emphasized the importance of A. limacinum as a viable microbial platform for environmentally friendly production of PUFA such as DHA. Also, the study reinforced the utility of CSIA in tracking PUFA metabolic fate, which has latent applications in biomedical research, particularly in neurodegenerative disease frameworks where DHA plays a vital role. Finally, these results may also contribute to understanding isotopic fractionation patterns and metabolic flux variations across different microalgal growth phases.